The influence of surface structure and thermal conductivity of the tube on the condensation heat transfer of R134a and R404A over single horizontal enhanced tubes. (October 2017) - Zhao, Chuang-Yao; Ji, Wen-Tao; Jin, Pu-Hang; Zhong, Ying-Jie; Tao, Wen-Quan
Highlights: The effects of tube's thermal conductivity on the plain and enhanced condensing tubes are studied. The filmwise condensation heat transfer performances of R134a and R404A are compared on the same condensing tubes. The influencing mechanisms of tube's thermal conductivity of the on the filmwise condensation heat transfer is elucidated. Abstract: The influences of tube's surface structure and thermal conductivity on the filmwise condensation of R134a and R404A are investigated on four single horizontal enhanced tubes with 2D and 3D finned structures. The test tubes are made of iron cupronickel and aluminum brass. The results indicate that the condensation heat transfer of R404A is more sensitive to surface structure and thermal conductivity than R134a; the 3D finned surface is more suitable than the 2D finned one to enhance the condensation heat transfer for the tubes with low thermal conductivity; the different material thermal conductivities produce different subcooling temperature distributions of the fins, and therefore provide different condensation heat transfer performances. Besides, the influencing mechanisms of the tube's thermal conductivity on condensation heat transfer are elucidated.